Labour localisation and human resource management practices in the Gulf countries - Waxin, Marie-France (2016)
The chapter is organized as follows: first, we examine the literature on core issues pertinent to this theme, such as demographic and labor-market characteristics in the GCC, the objectives of these localisation programs, and the major components of localisation policies. Second, we review the literature on HRM practices that facilitate the implementation of localisation programs. Third, we review multiple challenges related to the implementation of these programs. Finally, we present some recommendations intended to enhance the impact of localisation efforts.